Efficacy Assessment of Newly-designed Filtering Facemasks during the SARS-CoV-2 Pandemic - Bob Boogaard; Ali Tas; Joep Nijssen; Freek Broeren; John van den Dobbelsteen; Vincent Verhoeven; Jip Pluim; Sing Dekker; Eric J. Snijder; Martijn J. van Hemert; Sander Herfst (Aerosol and Air Quality Research)
Abstract The SARS-CoV-2 pandemic resulted in shortages of production and test capacity of FFP2-respirators. Such facemasks are required to be worn by healthcare professionals when performing aerosol-generating procedures on COVID-19 patients. In response to the high demand and short supply, we designed three models of facemasks that are suitable for local production. As these facemasks should meet the requirements of an FFP2-certified facemask, the newly-designed facemasks were tested on the filtration efficiency of the filter material, inward leakage, and breathing resistance with custom-made experimental setups. In these tests, the facemasks were benchmarked against a commercial FFP2 facemask. The filtration efficiency of the facemask’s filter material was also tested with coronavirus-loaded aerosols under physiologically relevant conditions. This multidisciplinary effort resulted in the design and production of facemasks that meet the FFP2 requirements, and which can be produced at local production facilities.